Determination of Nickel in Natural Water Samples by Flow Injection- Inductively Coupled Plasma Optical Emission Spectrometry - JAVAD POURSHARIFI., MOHAMAD; MOGHIMI, ALI (Asian Journal of Chemistry, 2010)
An on-line nickel preconcentration and determination system implemented with inductively coupled plasma optical emission spectrometry associated to flow injection was studied. Trace amounts of nickel were preconcentrated by sorption on a conical mini-column packed with activated carbon modified with a Schiff's base bis(2-hydroxyphenylamino) glyoxime at pH 5.0. The nickel was removed from the minicolumn with 20 % nitric acid. An enrichment factor of 80-fold for a sample volume of 50 mL was obtained. The detection limit value for the preconcentration method proposed was 70 ng L-1. The precision for 10 replicate determinations at the 0.6 µg L-1 Ni level was 2.2 % relative standard deviation, calculated from the peak heights obtained. The calibration graph preconcentration method for nickel was linear with a correlation coefficient of 0.9996 at levels near the detection limits up to at least 120 µg L-1. The method was successfully applied to the determination of nickel in natural water samples.